2022
DOI: 10.1111/jfpp.17042
|View full text |Cite
|
Sign up to set email alerts
|

Influence of processing techniques on the protein quality of major and minor millet crops: A review

Abstract: Millets have a distinctive protein composition comprising of high concentrations of essential amino acids with numerous health‐promoting characteristics. Through various in vitro and animal research studies, a variety of millet‐based bioactive peptides isolated from millets have given significant evidence of their health‐improving properties. However, the processing technique significantly impacts the biological activity of these millet peptides. The amount, structure, and function of major and minor millet pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 97 publications
1
7
0
Order By: Relevance
“…A total of 56 volatile compounds were identified in the millet Huangjiu samples, comprising 22 esters, 13 alcohols, 10 aldehydes, 6 acids, 3 phenolics, and 2 ketones, as shown in Table 3 . These results are generally consistent with previous reports on the volatile composition of other millet Huangjiu samples [ 4 , 10 , 12 ].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…A total of 56 volatile compounds were identified in the millet Huangjiu samples, comprising 22 esters, 13 alcohols, 10 aldehydes, 6 acids, 3 phenolics, and 2 ketones, as shown in Table 3 . These results are generally consistent with previous reports on the volatile composition of other millet Huangjiu samples [ 4 , 10 , 12 ].…”
Section: Resultssupporting
confidence: 93%
“…Previous research has suggested that the production of bitter peptides in sake is highly dependent on the glutelin content of rice grains [ 8 ], highlighting the significance of protein metabolism in shaping the flavor profile of fermented beverages. The development of bitterness in Huangjiu is thought to arise from an imbalance in protein hydrolysis and peptide hydrolysis, emphasizing the importance of carefully balancing the glutelin contents in raw materials to optimize wine quality [ 4 , 6 , 9 ]. Taken together, these findings suggest that carefully selecting the appropriate protein type and amount during the fermentation process is essential to achieving the desired taste profile in millet Huangjiu.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of processing on specific varieties of millet starches has also been reviewed by various researchers (Punia et al, 2021; Rathore et al, 2019). Concurrently, changes in specific nutritional properties namely, proteins, and starch, have been reviewed by some authors (Bangar et al, 2022; Mahajan et al, 2021). However, no dedicated comprehensive review on hydrothermal processing of millets for its value addition and development of hydrothermally processed millet‐based products has been published so far.…”
Section: Introductionmentioning
confidence: 99%
“…Previously published reviews have mostly reported on raw millet grains, their flours, and composite products based on millet flours in combination with other flours and ingredients (Gowda et al, 2022; Hassan et al, 2021; Saleh et al, 2013; Sharma et al, 2021; Yousaf et al, 2021). Most reviews are limited to the characterization of a single nutritional component (Bangar et al, 2022; Mahajan et al, 2021) and single or a few varieties of millets (Punia et al, 2021; Rathore et al, 2019). Considerable gaps exist in the knowledge related to the hydrothermal processing of grain and its relation with the techno‐functional characteristics.…”
Section: Introductionmentioning
confidence: 99%